Iridium and rhodium complexes bearing a silyl-bipyridine pincer ligand: synthesis, structures and catalytic activity for C–H borylation of arenes. Issue 26 (23rd June 2022) - Komuro, Takashi; Mochizuki, Daiki; Hashimoto, Hisako; Tobita, Hiromi
Abstract : The synthesis of five-coordinate 16e SiNN-pincer complexes of iridium and rhodium, and catalytic C(sp 2 )–H borylation under mild conditions are described. Abstract : Unsaturated 16-electron iridium and rhodium complexes bearing a silyl-bipyridine-based SiNN-pincer ligand (Bpy SiNN ) were synthesised and characterised by X-ray crystallography and NMR spectroscopy. The iridium-Bpy SiNN complex facilitated the catalytic C(sp 2 )–H borylation of arenes to give arylboronate esters in high yields (≥93%) under mild conditions (∼40 °C).